Bakteri Konsorsium dari Serasah Mangrove untuk Produksi Kompos (Organic Compost Production from Bacterial Consortium of Mangrove Leaf Litter) - Delianis Pringgenies (Program Studi Manajemen Sumber Daya Perairan, 2018)
Increasing of populations and activities has also increase the town waste, mainly of the organic waste. As nowadays had no comprehensive handled optimally. One option of organic waste processing is by compost production, by means of organic biodegradation. The aim of the research is to find out whether 4 types of bacteria, namely: Psedomonas sp., Flavobacterium sp., Acinetobacter sp., Bacillus subtilis are synergies into consortium bacteria, whether potential consortium bacteria as organic waste decomposing bacteria, how compost from bacteria consortium, , smell, color and temperature. The synergy bacteria test was performed by scraping four types of bacteria on Nutrien Broth medium (NB). Compost processing was done by application of bacterial consortium into the municipal organic waste and incubated for about 8 weeks. The results showed that four types of bacteria, namely: Pseudomonas sp., Flavobacterium sp., Acinetobacter sp., Bacillus subtilis is the synergy and potential as a consortium bacterium. Compost is formed after 4 weeks of incubation with crumbed texture, black color, soil like odor and temperature 28oC.Key words : Bacterial consortium, mangrove leaf litter, organic waste, composting.